A multiple behaviour temporal network analysis for health behaviours during COVID‐19 - Allen, Zack; Presseau, Justin (British journal of health psychology, 2024)
Objectives The aim of this study was to examine the temporal dynamics of multiple health behaviours (physical activity, alcohol consumption, healthy eating, cigarette consumption, recreational drug use, vaping), and pandemic‐related health behaviours (e.g., hand washing, physical distancing) using network psychometrics. Design The International COVID‐19 Awareness and Responses Evaluation (iCARE) study is an international multi‐wave observational cohort study of public awareness, attitudes, and responses to public health policies implemented to reduce the spread of COVID‐19 on people around the world. A sub‐sample of longitudinal data from Canadians (n = 254) was analysed across four waves (February–July 2020). Methods We used temporal network models to fit temporal networks, contemporaneous networks, and between‐subject networks from items within the iCARE survey. Results Positive temporal associations were observed between physical activity and healthy eating, and a bidirectional relationship was evident between outdoor mask use and vaping. A contemporaneous network revealed positive associations between consumption behaviours (vaping, cigarette use, alcohol use, and recreational drug use), and negative associations between physical activity and drug use, and healthy eating and cigarette use. Conclusions Health behaviours are interconnected and can be modelled as networks or behavioural systems. The application of temporal network analysis to the study of multiple health behaviours is well suited to address key research questions in the field such as ‘how do multiple health behaviours co‐vary with one another over time’. Future research using time series data and measuring affective and cognitive mediators of behaviour, in addition to health behaviours, has the potential to contribute valuable hypothesis‐generating insights.